PENGARUH WEBSITE QUALITY DAN E-SERVICE QUALITY TERHADAP E-LOYALTY DENGAN VARIABEL INTERVENING USER SATISFACTION PADA MAHASISWA FE UST YOGYAKARTA PENGGUNA SHOPEE - sherlyn deviana (JURNAL ILMIAH EDUNOMIKA, 2021)
Decision The purpose of this study was to examine the effect of the website on Shopee and service quality at Shopee on customer loyalty. The sampling technique in this study used a questionnaire distribution technique. And the object in this study is Shopee users (students) at the Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta with a sample size of 100 respondents. This object is a Shopee user who accidentally meets the researcher and the object is in accordance with the researchers' criteria to be used as a data source. The data obtained were then analyzed using the SPSS version 22 software application. The test was carried out with a hypothesis to determine whether there was an effect of variable X1 and variable X2 on variable Y with the intervening variable User Satisfaction. The results of this study prove that Website Quality and E-Service Quality on E-Loyalty through User Satisfaction in FE students at UST Yogyakarta, shopee customers and E-Service Quality have a positive effect on E-Loyalty is rejected.